¿Qué hacemos con nuestro hotel? - Llosa de Cárdenas, Fernando (Universidad ESAN. ESAN Ediciones, 1997)
Case study of a luxury hotel built in downtown Cusco in the late 1940s, when tourism in that city gained great momentum due to the global spread of the archaeological heritage located nearby. The business was success, but in the 1970s demand and revenues began to decline. The situation did not improve until 1993, when after years of accumulated debts, the hotel began to recover income, which allowed it to stay without major investments. Shortly after, the owner passed away, leaving a dilapidated hotel for his three sons. Now they must decide what to do with the hotel: sell it, rent it or operate it themselves or in association with another company. Unable to reach an agreement, they hire specialist consultants in the field to make a better decision. The case includes financial information and a summary of the consulting firm's study.

Estudio de caso de un hotel de lujo construido en el centro del Cusco a finales de la década de 1940, cuando el turismo en esa ciudad cobró gran impulso debido a la difusión global del patrimonio arqueológico ubicado en sus cercanías. El negocio fue un éxito, pero en la década de 1970 la demanda y los ingresos comenzaron a disminuir. La situación no mejoró hasta 1993, cuando tras años de deudas acumuladas, el hotel empezó a recuperar ingresos, lo que le permitió mantenerse sin grandes inversiones. Poco después, el propietario falleció, dejando un hotel en ruinas para sus tres hijos. Ahora deben decidir qué hacer con el hotel: venderlo, alquilarlo u operarlo ellos mismos o en asociación con otra empresa. Al no poder llegar a un acuerdo, contratan consultores especialistas en la materia para tomar una mejor decisión. El caso incluye información financiera y un resumen del estudio de la consultora.
Keywords: Tourism sector; Financial analysis; Sector turístico; Análisis financiero; Market analysis; Análisis de mercado; https://purl.org/pe-repo/ocde/ford#5.02.04